Synthesis, processing and testing of A poly(DL-lactide-CO-ε- caprolactone) resorbable electrospun membrane for guided tissue regeneration - Piyakunakorn P. (2014)
The aim of this study was to fabricate 75:25 poly(DL-lactide-co-ε- caprolactone), poly(DLL-co-CL) membranes for used in guided tissue regeneration (GTR). The copolymer was synthesized by ring-opening polymerization (ROP) in bulk. The 3-dimensional fiber networks with built-in microporosity membranes were prepared by electrospinning. The pore size was varied between 5-30 μm and the porosity of membrane was 69%. After immersing in phosphate buffered saline (PBS), the membranes were degradable with time, as indicated by molecular weight loss, mass weight loss, reduction of pH of the media and changes in the surface topography and shape of the membranes. However, the in vitro hydrolytic degradation of the membranes was too fast for use as periodontal GTR. The membranes maintained their original shape for the first 4 weeks and the porous structure disappeared within 2 weeks. Results from agar diffusion test suggest the membranes to be non-cytotoxic. In conclusion, the electrospun membrane was non-cytotoxic but the degradation rate was too fast to be used as GTR membrane in periodontal treatment. © (2012) Trans Tech Publications.